Using spent mushroom substrate (SMS) as a casing boosted bacterial activity and enhanced the mineral profile of the Calocybe indica - Raisa Bashir; Mahiea Hossain Mahi; Tasnimul Ferdous; Mohammad Abbas Gani; Sabrina M. Elias; Sabina Yesmin; Md. Shafiqul Islam; Jebunnahar Khandakar (Scientific Reports)
Abstract Recent extended summer seasons have presented considerable challenges for mushroom cultivation, underscoring the need for summer-adapted commercial varieties like Calocybe indica. The casing is essential for its cultivation, which conventionally employs loamy soil (LS). However, given the non-renewable nature of LS and the environmental concerns associated with spent mushroom substrate (SMS), our study explored SMS as a potential alternative. We analyzed the physio-chemical properties and microbial flora, especially bacterial composition, using MALDI-TOF in both LS and SMS. The total yield, biological efficiency, and mineral content of mushrooms grown on these substrates. While most of the physio-chemical properties of SMS align with the ideal casing properties, it exhibits higher electrical conductivity (EC) and a greater C/N ratio. The dominating bacterial flora in SMS, including Bacillus, Priestia, and Lysinbacillus, contribute to the mushrooms’ temperature tolerance and facilitate nutrient uptake, especially phosphorous (P). The yields and biological efficiency were significantly higher in LS, likely due to its superior mechanical support. Furthermore, the findings indicated that the qualities of element levels, particularly copper (Cu), zinc (Zn), and phosphorous (P), were markedly elevated in mushrooms grown on SMS, except for iron (Fe). The PCA biplot results further supported these findings. The significantly elevated phosphorus (P) level in mushrooms grown in SMS highlights the role of phosphorous-solubilizing bacteria in SMS. Interestingly, Calocybe indica consistently exhibited higher iron (Fe) content than Pleurotus ostreatus, irrespective of the casing material used. The metal bioaccumulation factors (BCF) reveal that Calocybe indica is a hyperaccumulator of potassium (K) but does not bioaccumulate manganese (Mn). It also showed a low accumulation level of calcium (Ca) and iron (Fe), suggesting a synergistic interaction between Ca and Fe. In conclusion, LS proved more effective in maximizing yield, while SMS emerged as a sustainable alternative, enhancing the nutritional content of mushrooms and presenting a feasible choice for ecologically aware farming.